Comparative nutritional evaluation of the leaves of selected plants from the Poaceae family (bamboos and grasses) for sustainable livestock production in Ghana - Sasu, Prince; Attoh-Kotoku, Victoria; Anim-Jnr, Antoinette S.; Osman, Alhassan; Adjei, Obed; Adjei-Mensah, Benjamin; Edinam Aku Akoli, Dora; Adjima Tankouano, Rachida; Kwaku, Michael; Obloni Kweitsu, Daniel (Frontiers in Sustainable Food Systems, 2023)
Background: Sustainable animal feeding is essential for reducing poverty among Ghanaian smallholder livestock farmers. However, seasonality has a severe impact on the availability and quality of conventional animal feedstuffs, necessitating the exploration of alternate feed sources. Objective: The goal of the study was to evaluate and contrast the feeding value of the leaves of conventional Poaceae plants (grasses), namely Cenchrus purpureus (CP), Megathyrsus maximus (MM), and Brachiaria decumbens (BD), non-conventional Poaceae plants (bamboos), notably Oxytenanthera abyssinica (OA), Bambusa balcooa (BB), and Bambusa vulgar (BV). Materials and methods: The leaves were subjected to the standard procedures of proximate and detergent fibre systems to highlight their nutritional value and estimates of dry matter intake, digestible dry matter, and relative feed value. Results: The results revealed that bamboo leaves had significantly (P < 0.05) higher mean dry matter (910.3 vs. 835.5 g/kgDM), crude protein (133.0 vs. 75.1 g/kgDM), EE (137.3 vs. 82.0 g/kgDM), ash (133.6 vs. 88.7 g/kgDM), and hemicellulose (79.3 vs. 27.9 g/kgDM), while the grasses relatively had higher (P < 0.05) mean acid detergent fibre (461.4 vs. 402.7 g/kgDM), cellulose (417.0 vs. 397.4 g/kgDM), and acid detergent lignin (5.0 vs. 0.4 g/kgDM). The bamboo leaves also gave higher (P < 0.05) estimates of dry matter intake (24.9 vs. 24.4 %), digestible dry matter (57.5 vs. 52.9 %), and relative feed value (111.1 vs. 104.6). Conclusion: In conclusion, bamboo leaves have exhibited high nutritional characteristics and could be used to complement or even replace conventional grasses in the diets of cattle, sheep, and goats, especially during the dry season when the availability and quality of animal feed significantly decrease. However, further studies should be conducted on the phytochemical (bioactive) compositions of bamboo leaves, and their effect on the intake and growth performance of animals to augment the findings so far.